1999
DOI: 10.2169/internalmedicine.38.296
|View full text |Cite
|
Sign up to set email alerts
|

Cytophagic Histiocytic Panniculitis Improved by Combined CHOP and Cyclosporin A Treatment.

Abstract: In a 31-year-old Japanese man with cytophagic histiocytic panniculitis (CHP) remission was achieved by a combination of combined chemotherapy CHOPand cyclosporin A treatment. He was admitted to our hospital in January 1994 with recurrent high fever of 40.2°C and tender and violaceous subcutaneous nodules on his trunk, arms and legs. Hedeveloped pancytopenia, hemorrhagic diathesis, liver dysfunction. Histological examination of the biopsied subcutaneous nodule revealed a lobular panniculitis with fat necrosis a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 34 publications
(13 reference statements)
1
16
0
Order By: Relevance
“…Long-term remission on cyclosporin is in contrast with panniculitis in the setting of SPTL, where cyclosporin is ineffective and a short clinical course with early demise is the rule [3,12]. Although initial diagnosis should nowadays be established by appropriate molecular studies to optimise treatment decisions, patients with CHP require close follow-up: cases of initially unapparent lymphoma evolving several years after CHP diagnosis have been reported [3,13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Long-term remission on cyclosporin is in contrast with panniculitis in the setting of SPTL, where cyclosporin is ineffective and a short clinical course with early demise is the rule [3,12]. Although initial diagnosis should nowadays be established by appropriate molecular studies to optimise treatment decisions, patients with CHP require close follow-up: cases of initially unapparent lymphoma evolving several years after CHP diagnosis have been reported [3,13].…”
Section: Discussionmentioning
confidence: 99%
“…Since 1990 the use of combined cytotoxic agents such as cyclophosphamide, doxorubicin, vincristine and prednisolone (CHOP) with or without combination with cyclosporin has seen the mortality rate decrease from 60% to approximately 24% [13], indicating that T-cell specific chemotherapy is optimal treatment for patients with CHP. Complete remission in our case was eventually achieved with the addition of cyclosporin.…”
Section: Discussionmentioning
confidence: 99%
“…However, there was no randomized controlled trial due to the rarity of the disease. Subsequent articles also demonstrated successful outcomes using either cyclosporin combined with CHOP or oral cyclosporin alone [10,11]. In one study [11], serum levels of interferon g and soluble interleukin-2 receptor were tremendously elevated during the active disease and normalized after cyclosporin, suggesting that cytokine modulation may be the mechanism of action of this drug.…”
Section: Discussionmentioning
confidence: 99%
“…Iwasaki et al 16 reported a patient with WCD with increased serum levels of soluble IL-2 receptor, IFN-γ, IL-6, IL-4, and IL-10, who was treated successfully with cyclosporin A. Cytophagic histiocytic panniculitis (CHP) can be a severe variant of Weber-Christian disease characterized by the histopathological appearance of lobular panniculitis infiltrated by T helper cells, and histiocytes containing blood cell fragments, and by a clinical course with marked systemic features, including multiorgan failure, hypertriglyceridemia, and coagulopathy, which may lead to death. [17][18][19] However, cyclosporine A is very effective in CHP. 17,19 From these findings and the case study reported here, it is suggested that T-cell immune responses may be involved in the pathogenesis of WCD.…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19] However, cyclosporine A is very effective in CHP. 17,19 From these findings and the case study reported here, it is suggested that T-cell immune responses may be involved in the pathogenesis of WCD. We recommend further study on the pathogenesis of WCD.…”
Section: Discussionmentioning
confidence: 99%